Pigmented areas of piebaldism. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
The pathogenesis of the islets of pigmented skin inside the white patches of piebaldism is not yet fully clarified, although so characteristic to make the diagnosis of piebaldism easier. Some Author hypothesized that they are reminiscent of "café-au-lait" spots, although the association with neurofibromatosis type I was never shown (1). We hypothesize a photo-induced pigmentation reminiscent of vitiligo, in which melanocytes lack as well as in piebaldism. In contrast, photo-induced pigmentation lacks in the white areas of nevus depigmentosus and tuberous sclerosis, where melanocytes are present, although not well functioning. This hypothesis is supported by the lack of pigmented areas at birth, as in the case here reported, and by the reported reduction or even disappearance of white patches of piebaldism (2).